Improved quality and efficiency after the introduction of physician-led team triage in an emergency department. (2nd January 2016) - Burström, Lena; Engström, Marie-Louise; Castrén, Maaret; Wiklund, Tony; Enlund, Mats
Abstract: Background : Overcrowding in the emergency department (ED) may negatively affect patient outcomes, so different triage models have been introduced to improve performance. Physician-led team triage obtains better results than other triage models. We compared efficiency and quality measures before and after reorganization of the triage model in the ED at our county hospital. Materials and methods : We retrospectively compared two study periods with different triage models: nurse triage in 2008 (baseline) and physician-led team triage in 2012 (follow-up). Physician-led team triage was in use during day-time and early evenings on weekdays. Data were collected from electronic medical charts and the National Mortality Register. Results : We included 20, 073 attendances in 2008 and 23, 765 in 2012. The time from registration to physician presentation decreased from 80 to 33 min ( P < 0.001), and the length of stay decreased from 219 to 185 min ( P < 0.001) from 2008 to 2012, respectively. All of the quality variables differed significantly between the two periods, with better results in 2012. The odds ratio for patients who left before being seen or before treatment was completed was 0.62 (95% confidence interval 0.54–0.72). The corresponding result for unscheduled returns was 0.36 (0.32–0.40), and for the mortality rates within 7 and 30 days 0.72 (0.59–0.88) and 0.84 (0.73–0.97), respectively. The admission rate was 37% at baseline and 32% at follow-up ( P < 0.001). Conclusion : Physician-led team triage improved the efficiency and quality in EDs.